Onomastic Code in the Works of Dina Rubina “Napoleon Convoy” and “The White Dove of Cordoba” - L. G. Kihney; E. S. Tulusheva (Научный диалог)
The semantic and plot-generating functions of the onomastic paradigm in the works of Dina Rubina “Napoleon wagon train” and “The White Dove of Cordoba” is examined in the article. The relevance of the study is due to the fact that the trilogy “Napoleon’s Wagon Train” has not previously been subjected to scientific analysis, nor has the artistic techniques of this trilogy been compared with those of other works by Dina Rubina. The novelty of the research is seen in the fact that, based on the material of the latest novels by Rubina, repeated motives of the reification and humanization of a name, giving it the status of an independent being, a character equal to the bearers of this name, are revealed. Attention is paid to the tendencies in the use of the onomastic code and its gravitation towards a certain type of characters, the life story of which is considered by the author in comparison with the characters who lose, hide and deliberately deform their names in an extensive chronotope, covering the period from the era of antiquity, the Renaissance and the Napoleonic wars to the present day. It is proved that the onomastic code, manifested in novels included in different trilogies, appears as a structural component cementing all the later novelistic works of Dina Rubina as the author’s supertext, arranged according to uniform semantic laws. The proper name in Rubina’s works is a meta-symbol, a sign of personality identification in its uniqueness and in the history of the clan and family.